CULTIVATING DOMINATION: ECOFEMINISM, THE LOGIC OF CONTROL, AND THE WHITE TIGER ORCHID IN UGLIES - Elsa Fitria Nasta; Muarifuddin Muarifuddin; Rahmawati Azi (Seshiski: Southeast Journal of Language and Literary Studies, 2026)
This study investigates the ecological irony embodied by the White Tiger Orchid as a symbol of energy revolution in the film Uglies (2024) through the lens of Karen J. Warren’s transformative ecofeminism. The film depicts a futuristic society that relies on a genetically engineered flower as a sustainable energy source; however, this technological innovation ultimately contributes to environmental degradation and mechanisms of social control. Employing a descriptive qualitative approach, this research analyzes dialogues, visual imagery, and narrative events to examine the interconnected domination of nature and women represented in the film. The findings reveal that the White Tiger Orchid serves not as a sustainable solution but as a tool of exploitation that operates through value-hierarchical thinking, value dualism, and the logic of domination. Similar patterns of oppression are reflected in The Transformation, a mandatory procedure that reconstructs human bodies while suppressing individuality and critical awareness. Furthermore, the film presents an alternative ecofeminist vision through The Smoke community and Tally Youngblood’s development of ecological consciousness, which challenges patriarchal structures of power. This study concludes that the White Tiger Orchid represents the paradox of technological progress that promises environmental sustainability while simultaneously reinforcing the domination of both nature and women.